Home learning profile of children in rural areas: A phenomenological study in Jember, East Java - Miftakhuddin; Kamil, Nurdin; Hardiansyah, Hadi (Universitas Nahdatul Ulama Surabaya, 2022)
This study strives to compile a home learning (LFH) profile of rural children. This study was conducted using a phenomenological design. Data were collected through in-depth interviews and participatory observations in 13 villages. The validity of the data is checked using source triangulation and technique triangulation. Based on the qualitative analysis, the following significant findings are highlighted: (a) children and parents view LFH as government reimbursement for a crisis circumstance, rather than as a school-mandated requirement. (b) LFH in rural areas is implemented in a blended learning design (model: flipped classroom). The design was adopted since the prior full-online and hybrid learning designs were ineffective. (c) LFH participation rates tend to be low. Besides being caused by technical constraints, this is due to the socio-cultural environment that promotes pragmatism in the educational process. (d) Through the Madurese philosophy of Bhuppa'-Bhabbhu', Ghuru, Rato, the socio-cultural context gives prospects for the success of LFH and the growth of education in general. This concept serves as a guideline for the Madurese ethnic community to establish priorities and respect for three (or four) key figures in life according to Islamic tradition. underpins the child's decision to participate in LFH or not. The findings of this study have the potential to correct a number of prior studies that identified poverty and underdevelopment as the most influential determinants in the success of rural children's home learning.